Functional characterization of VirB/VirD4 and Icm/Dot type IV secretion systems from the plant-pathogenic bacterium Xanthomonas euvesicatoria - Drehkopf, Sabine; Scheibner, Felix; Büttner, Daniela (Frontiers in Cellular and Infection Microbiology, 2023)
Many Gram-negative plant- and animal-pathogenic bacteria employ type IV secretion (T4S) systems to transport proteins or DNA/protein complexes into eukaryotic or bacterial target cells. T4S systems have been divided into minimized and expanded T4S systems and resemble the VirB/VirD4 T4S system from the plant pathogen Agrobacterium tumefaciens and the Icm/Dot T4S system from the human pathogen Legionella pneumophila, respectively. The only known plant pathogen with both types of T4S systems is Xanthomonas euvesicatoria which is the causal agent of bacterial spot disease on pepper and tomato plants. In the present study, we show that virB/virD4 and icm/dot T4S genes are expressed and encode components of oligomeric complexes corresponding to known assemblies of VirB/VirD4 and Icm/Dot proteins. Both T4S systems are dispensable for the interaction of X. euvesicatoria with its host plants and do not seem to confer contact-dependent lysis of other bacteria, which was previously shown for the chromosomally encoded VirB/VirD4 T4S system from Xanthomonas axonopodis pv. citri. The corresponding chromosomal T4S gene cluster from X. euvesicatoria is incomplete, however, the second plasmid-localized vir gene cluster encodes a functional VirB/VirD4 T4S system which contributes to plasmid transfer. In agreement with this finding, we identified the predicted relaxase TraI as substrate of the T4S systems from X. euvesicatoria. TraI and additional candidate T4S substrates with homology to T4S effectors from X. axonopodis pv. citri interact with the T4S coupling protein VirD4. Interestingly, however, the predicted C-terminal VirD4-binding sites are not sufficient for T4S, suggesting the contribution of additional yet unknown mechanisms to the targeting of T4S substrates from X. euvesicatoria to both VirB/VirD4 and Icm/Dot T4S systems.